Modelling the fate and transport of oil spills - Barreto, Fernando Tulio Camilo (2019)
The consequence associated with oil spills in water bodies goes beyond the dreadful environmental damages, causing a great economical loss and health issues for the population. To minimize its damage, the application of computational models that predict the evolution of oil slicks is a powerful supporting tool in the mitigation of oil spill accidents. In this thesis we constructed an open source three dimensional oil spill fate and transport model (available at https://github.com/fernandotcbarreto/SYMOS-model), employing state-of-art parametrizations for the physical-chemical processes undergone by the oil, and the lagrangian parcel method to resolve the advection and turbulent diffusion of the slick. To overcome the unpredictable nature of oil spills we implemented a probabilistic method that simulates a great number of scenarios under different meteoceanographic conditions, from which were calculated statistical parameters that allow a thorough description of the impacts by the oil slick.The transport and the four physical-chemical weathering processes implemented in the model, evaporation, emulsification, dissolution, and vertical dispersion (entrainment), were validated against measured and theoretical data, giving good correlations. After the validation of the model, it was applied to a study case in the Espírito Santo- Vitória bay system (SEIV), a region with intense port activities, to evaluated the sensibility of the study region to oil spills. For this evaluation, were performed probabilistic and continuous simulations for hypothetical spills in two locations of intense traffic of vessels, the entrance of Vitória bay (Vitória bay spill) and near Tubarão port (Tubarão port spill). The simulations were reproduced for a period of summer and winter to account for the seasonal variability in the analysis. For the Vitória bay spill, the statistical maps showed a small variability between summer and winter, with the most affected areas situated in the entrance of the Vitória bay and in the nearby Espírito Santo bay. This case was highly controlled by the tidal regime, with the slick dynamics reproducing the ebb dominance of the local current system. For the Tubarão port spill, on the contrary, there was a great variability between summer and winter. For summer, it was observed a clear tendency for the spill to propagate towards Camburi beach, and for winter all deterministic cases showed a transport outwards of the SEIV. For the continuous case the worst scenario for the study region was the Tubarão port spill in summer, since a great area of the SEIV and all extension of the Camburi beach was affected by the spill.